2019
DOI: 10.1038/s41438-019-0155-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling reveals the roles of pigment mechanisms in postharvest broccoli yellowing

Abstract: Postharvest broccoli is prone to yellowing during storage, which is the key factor leading to a reduction in value. To explore appropriate control methods, it is important to understand the mechanisms of yellowing. We analyzed the genes related to the metabolism of chlorophyll, carotenoids, and flavonoids and the transcription factors (TFs) involved in broccoli yellowing using transcriptome sequencing profiling. Broccoli stored at 10 °C showed slight yellowing on postharvest day 5 and serious symptoms on day 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 55 publications
(50 reference statements)
0
19
0
Order By: Relevance
“…Various TFs in Arabidopsis such as NACs (AtNAC046 and AtORE1), bHLHs (AtPIF4 and AtPIF5), and ethylene insensitive 3 (AtEIN3) have been shown to significantly enhance leaf senescence by promoting the activity of genes related to chlorophyll degradation ( Song et al , 2014 ; Qiu et al , 2015 ; Zhang et al , 2015 ; Oda-Yamamizo et al , 2016 ). In broccoli ( Brassica oleracea ), the MYB, bHLH, and bZIP gene families are associated with chlorophyll metabolism while NACs and ERFs regulate carotenoid biosynthesis ( Luo et al , 2019 ). CitERF6 and CitERF13 have also been associated with chlorophyll degradation during ethylene-induced and natural peel degreening in citrus ( Yin et al , 2016 ; Li et al , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various TFs in Arabidopsis such as NACs (AtNAC046 and AtORE1), bHLHs (AtPIF4 and AtPIF5), and ethylene insensitive 3 (AtEIN3) have been shown to significantly enhance leaf senescence by promoting the activity of genes related to chlorophyll degradation ( Song et al , 2014 ; Qiu et al , 2015 ; Zhang et al , 2015 ; Oda-Yamamizo et al , 2016 ). In broccoli ( Brassica oleracea ), the MYB, bHLH, and bZIP gene families are associated with chlorophyll metabolism while NACs and ERFs regulate carotenoid biosynthesis ( Luo et al , 2019 ). CitERF6 and CitERF13 have also been associated with chlorophyll degradation during ethylene-induced and natural peel degreening in citrus ( Yin et al , 2016 ; Li et al , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…HTSeq v0.5.4p3 was used to count the number of reads mapped to each gene or exon region 73 . The read counts for each gene were normalized by the FPKM 74 (fragments per kilobase of transcript per million mapped reads) method, which is often used for estimating gene expression levels. To reveal the variations in the datasets between the chilling and freezing stress levels, a cutoff of FPKM ≥ 0.01 was selected to define potentially meaningful gene expression.…”
Section: Gene Expression Quantification and Principal Component Analymentioning
confidence: 99%
“…Studies of C. humilis fruit color have revealed that in addition to DEGs, TFs play a key role in the regulation of color changes and the activity of pigment biosynthetic pathways [35]. MYB TFs contribute to the regulation of plant secondary metabolism, including anthocyanin biosynthesis [26,36].…”
Section: Discussionmentioning
confidence: 99%